Innovation activity in Ukraine: state, problems and legal framework improving perspectives - Shovkalіuk, V.; Chaika, D. (Наука, технології, інновації, 2017)
Ukraine has rich natural resources and is a leading global manufacturer of number of agricultural and industrial goods. However, the innovation level of companies and their production of goods with high added value is low. Article provides view Ministry of Education and Science of Ukraine initiatives of necessary changes in the regulatory and institutional field that regulates innovation.